Perception of Respiratory Sensation Assessed by Means of Histamine Challenge and Threshold Loading Tests - Bijl-Hofland, Ingrid D.; Cloosterman, Sonja G.M.; van Schayck, Constant P.; v. d. Elshout, Frank J.J.; Akkermans, Reinier P.; Folgering, Hans Th.M. (Chest, 2000)
Some asthmatic patients perceive the severity of their disease rather poorly. These patients may not receive optimal therapy because of underpresentation of their respiratory symptoms. It is therefore important to identify these patients. The present study evaluates a new threshold loading device for measuring the perception of respiratory sensation. This method for measuring the perception of respiratory sensation may be a viable alternative to the bronchial provocation test. The aim of the present study was to investigate whether the assessment of the perception of respiratory sensation based on a threshold loading test (inspiratory and expiratory) identifies the same subjects as poor perceivers as compared to assessment by histamine bronchial provocation test. In 36 subjects, the perception of respiratory sensation through a threshold loading device was compared to the perception of respiratory sensation during a histamine provocation test. Each test was performed with scoring of the magnitude of the respiratory sensation on a visual analog scale (VAS). The magnitude of the stimulus intensity was indicated by the percentage of decrease in FEV1 during the histamine challenge test and by the percentage of the subject's maximum mouth pressure (percent maximal inspiratory pressure and percent maximal expiratory pressure) during the threshold loading test. The relationship between VAS values and the stimulus intensity was analyzed by determining the linear regression coefficient between the two parameters. No relationship was found between the perception of the sensation induced by the histamine challenge and that during breathing through a threshold loading device for both inspiration (Rs = 0.15; p = 0.40) and expiration (Rs = 0.13; p = 0.47). We did find a significant relation between the perception of respiratory sensation during the inspiratory and expiratory threshold loading test (Rs = 0.67; p = 0.0001). Furthermore, we defined a subgroup of patients of special interest: those with low symptoms of breathlessness and high bronchial responsiveness. Compared to the inspiratory and expiratory threshold loading test, the histamine challenge test identified more patients in the special interest group as poorest perceivers. The measurement of perception by means of a threshold loading device and a histamine provocation test did not identify the same subjects as poor perceivers, probably because we did not measure the patient's perceptiveness for exactly the same stimuli. In the population with relatively more severe asthma and very low symptoms of breathlessness, the histamine-induced bronchoconstriction test identified more patients as poorest perceivers compared to the threshold loading test.